Zuhud dan Apatheia Dua Wajah Pengendalian Diri dalam Lanskap Pendidikan Karakter - Imam Mustakim (Jurnal Budi Pekerti Agama Islam, 2025)
This article offers a philosophical exploration of two classical concepts of self-control: zuhud in Islamic intellectual tradition and apatheia in Stoic philosophy, within the framework of modern character education. Using a qualitative library research approach, this study employs content analysis and philosophical hermeneutics to examine the works of key thinkers such as Al-Ghazali, Ibn Qayyim al-Jawziyyah, Marcus Aurelius, and Epictetus. The findings indicate that zuhud emphasizes detachment from material desires through spiritual awareness and prioritization of divine values, while apatheia focuses on achieving inner peace and moral clarity by rationally managing emotions and eliminating unnecessary passions. Although rooted in different theological worldviews, both concepts converge in promoting a form of self-control that enhances inner freedom, ethical behavior, and self-discipline. This study argues that the integration of zuhud and apatheia can enrich contemporary character education by balancing rational moral reasoning with spiritual consciousness. The educational model proposed in this research emphasizes the importance of teaching students to reflect critically, regulate their emotions, and cultivate inner balance rooted in universal ethical values. Thus, the synthesis of both traditions contributes to the advancement of character education that is holistic, contemplative, and morally grounded.